Penatalaksanaan Fisioterapi pada Kondisi Delay Development e.c Pneumonia dengan Modalitas Neuro Denso (NS), Neuro Development Treatment (NDT) dan Massage pada Otot-Otot Pernafasan di YPAC Prof. Dr. Soeharso Surakarta - Rakasiwi, Andung Maheswara; Ahsani, Devi Salma (Jurnal Keperawatan Mandira Cendikia, 2022)
One of the most common child development problems is Delay Development (DD), which is a significant lag in the physical development, cognitive, behavioral, emotional, or social development of a child when compared to normal children his age, a child with a disorder will be delayed in achieving one or more developmental abilities. Research Objectives: To determine the administration of neuro senso (NS) in improving the sensory system and activating motor programs, to determine the administration of neuro development treatment (NDT) in increasing functional activity, and massage on the respiratory muscles in minimizing the presence of sputum/phlegm. Research Subject : In the condition of Delay development ec Pneumonia, physiotherapy intervention will be given using the neuro senso (NS), neuro delay development (NDT) method, and massage on the respiratory muscles. Methods: In this study, the author uses descriptive analytical method to determine the assessment and changes that can be known. Research Results: After 1 time of therapy, the results were obtained shortly after therapy, the patient's parents felt the patient was more regular in his sleep cycle, and the patient lost sputum/phlegm through feces, and after walking 3 times therapy the child was able to stand for a long time with the help of holding. and weight increased by 0.01 kg. Conclusion: Based on the discussion that has been put forward about Physiotherapy Management in the case of Delay Development ec Pneumonia with a patient on behalf of An V, the age of 1 year 1 month 6 days has several problems, namely 1) the presence of postural muscle hypotonus in the rectus abdominis muscle and gluteus maximus muscle, 2 ) The presence of motor delays and sensory disturbances, 3) The presence of sputum. Key word: Neuro Senso,Developmental Delay, Neuro Development Treatment, Massage on respiratory muscles